1976
DOI: 10.1007/bf00328484
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of RNA polymerase on Drosophila polytene chromosomes as studied by indirect immunofluorescence

Abstract: Using indirect immunofluorescence visualization techniques we investigated the in situ distribution of RNA polymerase B on Drosophila melanogaster polytene chromosomes. The enzyme was found at many sites distributed throughout the genome in a pattern clearly distinct from that observed for histone H1, but it was especially concentrated in puffs induced by heat shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
1
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 20 publications
5
22
1
1
Order By: Relevance
“…I (a)) illustrates the fact that the specific antibodies used did not bind to RNA polymerases I present in nucleoli of amphibian cells, in agreement with results obtained with salivary gland nuclei from D. melanogaster (Jamrich et al, 1978). Similar non-cross-reacting antibodies have been reported by Kedinger et al (1974), Somers et al (1975) and Lobban et al (1976) , whereas cross-reaction between RNA polymerases land II has been reported for other antibody preparations (Hildebrandt et al , 1973 ;Ingles, 1973 ;Greenleaf et al, 1976;Buhler et al, 1976Buhler et al, ,1980Guilfoyle, 1980). Essentially similar results were obtained with the monoclonal murine antibodies (Fig.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…I (a)) illustrates the fact that the specific antibodies used did not bind to RNA polymerases I present in nucleoli of amphibian cells, in agreement with results obtained with salivary gland nuclei from D. melanogaster (Jamrich et al, 1978). Similar non-cross-reacting antibodies have been reported by Kedinger et al (1974), Somers et al (1975) and Lobban et al (1976) , whereas cross-reaction between RNA polymerases land II has been reported for other antibody preparations (Hildebrandt et al , 1973 ;Ingles, 1973 ;Greenleaf et al, 1976;Buhler et al, 1976Buhler et al, ,1980Guilfoyle, 1980). Essentially similar results were obtained with the monoclonal murine antibodies (Fig.…”
Section: Resultssupporting
confidence: 85%
“…Antibodies raised in rabbits against purified RNA polymerase II (B) from Drosophila melanogaster (Greenleaf & Bautz , 1975) and monoclonal antibodies to defined RNA polymerase II subunits of the same insect (Krämer et al, 1980) have been successfully used to study the distribution of this enzyme on polytene 81 0022-2836/81/250081 -19 $02 .00/0 chromosomes and in cu ltured cells by immunofluorescence microscopy (Plagens et al , 1976 ;Jamrich et al , 1977Jamrich et al , ,1978Krämer et al , 1980). While this experimental approach exploits the specific binding of the antibodies to the antigen for detecting and localizing the enzyme in situ, we became interested in the question of whether the binding of the antibody would also interfere with tran scrip ti on al events in the living cel!.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the availability of antibodies raised against Drosophila RNA polymerase (RNA nucleotidyltransferase) B (6) we possess a probe to study the localization of a chromosomal protein of known function. Upon treatment of squash preparations from D. melanogaster salivary glands, Plagens et al observed a distinct fluorescence pattern with the indirect immunofluorescence technique (7). They observed the a-amanitin-sensitive RNA polymerase B (also called polymerase II) not only in positions of visible puffs, but also at numerous other sites along the polytene chromosomes.…”
mentioning
confidence: 99%
“…The processes detectable in the nucleus include the induction of the heat shock puffs (1), the accumulation of proteins at the puff sites (22,23), redistribution of RNA polymerase II (24)(25)(26), onset of RNA transcription from the newly induced puffs (2,22,27) as well as changes in RNA processing (4,28,29) and the repression of other puffs. These dramatic changes at different levels of regulation may be accompanied by changes in nuclear proteins and the heat-shock specific pro- weight (46 000) from the cytoplasm suggests a migration to the nucleus of this protein very early after heat shock.…”
Section: Discussionmentioning
confidence: 99%